2018
DOI: 10.48550/arxiv.1801.09946
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

"23andMe confirms: I'm super white" -- Analyzing Twitter Discourse On Genetic Testing

Abstract: Recent progress in genomics is bringing genetic testing to the masses. Participatory public initiatives are underway to sequence the genome of millions of volunteers, and a new market is booming with a number of companies like 23andMe and AncestryDNA offering affordable tests directly to consumers. Consequently, news, experiences, and views on genetic testing are increasingly shared and discussed online and on social networks like Twitter. In this paper, we present a large-scale analysis of Twitter discourse o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…In followup work (Panofsky and Donovan 2019), they also look at the relationship between citizen science and white nationalists' use of genetic testing, shedding light on how "repair strategies" combine anti-scientific attacks on the legitimacy of these tests and reinterpretations of them in terms of white nationalist histories. (Mittos, Blackburn, and De Cristofaro 2018) conduct a study of the Twitter discourse on genetic testing, examining 300K tweets, and find that those who are interested in genetic testing appear to be tech-savvy and interested in digital health in general. They also find sporadic instances of users using genetic testing in a racist context, and others who express privacy concerns.…”
Section: Related Workmentioning
confidence: 99%
“…In followup work (Panofsky and Donovan 2019), they also look at the relationship between citizen science and white nationalists' use of genetic testing, shedding light on how "repair strategies" combine anti-scientific attacks on the legitimacy of these tests and reinterpretations of them in terms of white nationalist histories. (Mittos, Blackburn, and De Cristofaro 2018) conduct a study of the Twitter discourse on genetic testing, examining 300K tweets, and find that those who are interested in genetic testing appear to be tech-savvy and interested in digital health in general. They also find sporadic instances of users using genetic testing in a racist context, and others who express privacy concerns.…”
Section: Related Workmentioning
confidence: 99%
“…User generated content in online environments has proven helpful for researchers to investigate a broad range of topics (Mejova, Abbar, and Haddadi 2016;De Choudhury et al 2016). However, only a few studies have focused on mining the online disclosure of DTC genetic testing results in Twitter (Olejnik, Agnieszka, and Castelluccia 2014;Mittos, Blackburn, and De Cristofaro 2018). Moreover, besides the aforementioned research topics, few studies investigated the extent to which actual consumers applied and discussed their experiences regarding kinship, another popular application of DTC genetic testing.…”
Section: Social Computingmentioning
confidence: 99%
“…For instance, it was shown that Twitter users often post their ethnic background more than other information, such as disease risks, with respect to testing results (Olejnik, Agnieszka, and Castelluc-cia 2014). More recently, a large-scale analysis of Twitter discourse related to DTC genetic testing indicated that this behavior was often influenced by news and DTC websites (Mittos, Blackburn, and De Cristofaro 2018). Though there is a large population on Twitter who have disclosed their test results, it is difficult for Twitter users to develop rich discussions due to the limited number of characters in a tweet and its design as an all-purpose discussion environment.…”
Section: Introductionmentioning
confidence: 99%
“…Extant research regarding DTC genetic testing on social media confirms this lack of understanding. Prior research focuses on microblogging services such as Twitter [ 25 , 26 ], Reddit [ 27 ], or 4chan [ 18 ] to investigate user discourse on DTC genetic testing and shows that we are still puzzled about users' interests and opinions toward DTC genetic testing. Inconsistent findings regarding which topics users discuss on different platforms (eg, ancestry testing on Twitter [ 25 ] and health testing on Reddit [ 27 ]) suggest that the DTC genetic testing discourse varies from platform to platform and must thus be investigated separately.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research focuses on microblogging services such as Twitter [ 25 , 26 ], Reddit [ 27 ], or 4chan [ 18 ] to investigate user discourse on DTC genetic testing and shows that we are still puzzled about users' interests and opinions toward DTC genetic testing. Inconsistent findings regarding which topics users discuss on different platforms (eg, ancestry testing on Twitter [ 25 ] and health testing on Reddit [ 27 ]) suggest that the DTC genetic testing discourse varies from platform to platform and must thus be investigated separately. Moreover, research has already shown the value of analyzing users' opinions and attitudes through user comments from select platforms for DTC genetic testing–related content.…”
Section: Introductionmentioning
confidence: 99%